Animal models for clinical and gestational diabetes: maternal and fetal outcomes - Kiss, Ana C. I. [UNESP]; Lima, Paula H. O. [UNESP]; Sinzato, Yuri K. [UNESP]; Takaku, Mariana [UNESP]; Takeno, Marisa A. [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, Débora Cristina [UNESP] (Biomed Central Ltd., 2009)
Background: Diabetes in pregnant women is associated with an increased risk of maternal and neonatal morbidity and remains a significant medical challenge. Diabetes during pregnancy may be divided into clinical diabetes and gestational diabetes. Experimental models are developed with the purpose of enhancing understanding of the pathophysiological mechanisms of diseases that affect humans. With regard to diabetes in pregnancy, experimental findings from models will lead to the development of treatment strategies to maintain a normal metabolic intrauterine milieu, improving perinatal development by preventing fetal growth restriction or macrosomia. Based on animal models of diabetes during pregnancy previously reported in the medical literature, the present study aimed to compare the impact of streptozotocin-induced severe (glycemia >300 mg/dl) and mild diabetes (glycemia between 120 and 300 mg/dl) on glycemia and maternal reproductive and fetal outcomes of Wistar rats to evaluate whether the animal model reproduces the maternal and perinatal results of clinical and gestational diabetes in humans.Methods: on day 5 of life, 96 female Wistar rats were assigned to three experimental groups: control (n = 16), severe (n = 50) and mild diabetes (n = 30). At day 90 of life, rats were mated. on day 21 of pregnancy, rats were killed and their uterine horns were exposed to count implantation and fetus numbers to determine pre- and post-implantation loss rates. The fetuses were classified according to their birth weight.Results: Severe and mild diabetic dams showed different glycemic responses during pregnancy, impairing fetal glycemia and weight, confirming that maternal glycemia is directly associated with fetal development. Newborns from severe diabetic mothers presented growth restriction, but mild diabetic mothers were not associated with an increased rate of macrosomic fetuses.Conclusion: Experimental models of severe diabetes during pregnancy reproduced maternal and fetal outcomes of pregnant women presenting uncontrolled clinical diabetes. on the other hand, the mild diabetes model caused mild hyperglycemia during pregnancy, although it was not enough to reproduce the increased rate of macrosomic fetuses seen in women with gestational diabetes.